Copper oxide nanoparticles as an effective anti-biofilm agent against a copper tolerant marine bacterium, Staphylococcus lentus. Issue 9 (21st October 2019) - Padmavathi, Alwar Ramanujam; Sriyutha Murthy, P.; Das, Arindam; Nishad, Padala Abdul; Pandian, Ramanathasamy; Rao, Toleti Subba
Abstract: Biofilm formation on antifouling coatings is a serious concern in seawater cooling systems and the maritime industry. A prolific biofilm forming strain ( Staphylococcus lentus ), possessing high tolerance (>1, 000 µg ml −1 ) to dissolved copper ions (Cu ++ ) was isolated from titanium coupons exposed in the coastal waters of Kalpakkam, east coast of India. S. lentus formed increased biofilm ( p < 0.05) at 100 µg ml −1 of Cu ++ ions, when compared with the untreated control. To combat biofilm formation of this strain, the efficacy of copper oxide nanoparticles synthesized from copper nitrate by varying the concentrations of hexamine and cetyl trimethyl ammonium bromide (CTAB), was investigated. Complete (100%) inhibition of biofilm formation was observed with plain CuO NP (0.5 M hexamine, uncapped) at 1, 000 µg ml −1 . Capping with CTAB, influenced the morphology and the purity of the synthesized CuO NPs but did not alter their surface charge. Capping reduced metal ion release from CuO NPs and their antibacterial and anti-biofilm property against S. lentus. Overall, uncapped CuO NPs were effective in controlling biofilm formation of S. lentus . Concurrent release of copper ions and contact mediated physical damage by CuO NPs offer a promising approach to tackle metal tolerant biofilm bacteria.